Impact of the actions implemented in the integral solid waste management, in the Costa Rican Institute of Technology - Rodríguez-Rodríguez, Alina (2021)
One of the biggest challenges that Costa Rica is facing due to the climate change is to carry out a proper management of residues, because at the present time they represent one of the most important sources of CO2e emissions in the national territory. The Costa Rican Institute of Technology, from the Unidad Institucional de Gestión Ambiental y Seguridad Laboral,  joins the efforts of the country by formulating  different initiatives that seek to reduce the amount of solid waste that is disposed in the landfill, and guiding actions not only to manage them properly, but to prevent its continuing production. In a study of characterization of the ordinary solid waste from the central campus, it was determined that in 2016 the University sent 124 533 kg to the landfill, 19% of which corresponded to recycling materials that could have been managed by the Institutional Collection Center. Thus, via the implementation of clear and concise strategies, in 2018 the University reduced 57% of plastic waste and 50% of polylaminated waste, both sent before to the landfill. Besides, for the year 2019, the per capita waste production of the student residences was reduced by 47%, that means 22 856 kg of CO2e less in that year, an action consistent with the Carbon-Neutrality Management System of the University.